Idéologie : le mot, l’idée, la chose - Pierre Macherey (Methodos, 2008)
This paper studies the transvaluation of “ideology” as a neologism. Between 1796 (when the notion of “ideology” was invented by Destutt de Tracy) and 1845 (when it was reused by Marx), “ideology” changed its positive value (it refers to a general science of ideas) into a negative one (because it was referred to a social system of believes, shifted from the reality it mentions).